Differences in road-crossing decisions between healthy older adults and patients with Alzheimer's disease. (September 2018) - Fang, Chen-Wen; Lin, Chin-Hsien; Liu, Yung-Ching; Ou, Yang-Kun
Abstract: Introduction: This study investigated the differences in road-crossing behavior among healthy older adults and patients with Alzheimer's disease (AD). Method: Twelve pedestrians with mild AD and 24 age-, gender-, and education-matched controls were examined with a battery of cognitive, visual, and motor tests. Using a simulated two-lane, one-way road-crossing situation, we determined the remaining time and safety margin for each participant in traffic situations involving different vehicle speeds (40 km/h vs. 60 km/h vs. 80 km/h), time gaps (5 s vs. 7 s vs. 9 s), and time of day (dusk vs. midday). Results: We found that patients with AD were more vulnerable to traffic crash while crossing the road than healthy older adults (Odds Ratio = 2.50, P < 0.05). Compared with healthy older adults, patients with AD were more severely affected by daylight conditions, faster vehicle speed, and shorter time gap. Participants in both groups had a significantly higher risk of unsafe crossing behavior if they had lower scores on the Mini-Mental State Examination (MMSE), Complex Figure Test - recall (CFT-Recall), Trail Making Test (TMT) B-A, Useful Field of View (UFOV) - total, and Visual Form Discrimination (VFD). We also found that when given a long enough time gap (9 s), patients with AD and healthy older adults used similar safe road-crossing behaviors, independent of other factors. Practical applications: These results provide important suggestions for road design for patients with AD and healthy older adults during road-crossing. Highlights: Patients with mild Alzheimer's disease are at an increased risk of traffic accidents than control subjects. The risk of crossing road was correlated with the cognitive deterioration of Alzheimer's disease. Traffic environment factors were associated with worsening of safety errors in patients with Alzheimer's disease.